Selection of the insulation materials for refurbishment purposes. Issue 2 (3rd April 2017) - Lill, Irene; Kanapeckiene, Loreta; Tupenaite, Laura; Naimaviciene, Jurga
Abstract: Refurbishment of the building façades of residential buildings, including insulation, is often considered as the most energy efficient renovation measure with the largest potential. One of the solutions to increase energy efficiency is the selection of the appropriate insulation materials of the external walls. The article proposes the approach for selection of the insulation material based on SAW multiple criteria assessment method. The proposed methodology is applied for the case of insulation material selection in refurbishment of 12-storey building in Vilnius, Lithuania. Research reveals that rock wool outperforms other materials by thermal conductivity, light weigh, water vapour diffusion resistance, highest flammability class, durability and lowest emission of CO2 and is an efficient insulation to be used for sustainable refurbishment solutions.